Information acquisition and strategic disclosure in oligopoly - Jos Jansen (Max Planck Institute for Research on Collective Goods, 2007)
I study the incentives of oligopolists to acquire and disclose information on a common demand intercept. Since firms may fail to acquire information even when they invest in information acquisition, firms can credibly conceal unfavorable news while disclosing favorable news. Firms may earn higher expected profits under such a selective disclosure regime than under the regimes where firms commit to share all or no information. In particular, this holds under both Cournot and Bertrand competition, if the firms have sufficiently flat information acquisition cost functions. For steeper cost functions Cournot duopolists prefer strategic disclosure, if their goods are sufficiently differentiated.
Keywords: D82; D83; L13; L40; 330; oligopolistic competition; information acquisition; information sharing; commitment; common value; product differentiation; Informationsverhalten; Informationsaustausch; Oligopol; Wettbewerb; Produktdifferenzierung; Theorie